Return Rates for Needle Exchange Programs: A Common Criticism Answered - Ksobiech Kate (BMC, 2004)
Abstract This study searched the available needle exchange program (NEP) literature for return rate data. A total of 26 articles were found. The overall worldwide return rate was 90%, although this ranged from a low of 15% to a high of 112%. U.S. NEP return rates were gathered from only eight studies, indicating a clear need for more data, although U.S. return rates were comparable to those from NEPs outside of the U.S. One underlying assumption made by opponents of NEPs is that IDUs will not return needles to the distribution site, thereby potentially increasing the risk of health problems to the surrounding community from exposure to contaminated needles. This study's results suggest that NEPs are relatively successful in taking in used needles, although it is generally unclear where the needles were originally acquired, and if IDUs return their own needles, or are returning needles for a social network. Ways for AIDS Service Organizations to capitalize on these brief encounters with IDUs, as well as public policy implications of the findings, are discussed.